Prioritising the participation of IDPs in driving solutions - GP20 Colombia (Refugee Studies Centre, University of Oxford, 2020)
Participatory spaces – like those organised as part of the GP20 initiative in Colombia – must be maintained and expanded so that IDPs can work directly with local and national decision-makers in order to identify and take up opportunities to achieve durable solutions.